OF THE HUMANITIES AND THE PHILOSOPHICAL DISCIPLINE: The Right to Philosophy from the Cosmopolitical Point of View (the Example of an International Institution) - Derrida, Jacques (Surfaces, 1994)
This essay engages in a rethinking of the right to philosophy in its international dimension. It grounds its reflections in a reading of Kant's "Idea of a Universal History from a Cosmopolitical Point of View", considering the essay in terms of its implications for institutions founded after World War II. In examining these implications, it discusses issues of Eurocentrism, the founding history of modernity, and the role of UNESCO in posing the question of contemporary philosophy.